GreenPHABLETTM video for effective information dissemination on hermetic groundnut storage technology: GreenPHABLETTM VIDEO FOR DISSEMINATION ON GROUNDNUT STORAGE TECHNOLOGY - V V SUMANTHKUMAR; P VIJAYRAJU; S HARI KISHAN; D KUMARA CHARYULU; T CHAKRADHAR; CHAKRAVARTY AMIT; K V RAO; P MADHURI (Journal of Oilseeds Research, 2017)
Information and communication technologies (ICT) tools can facilitate dissemination of need based and farmer centric information at an affordable cost to India’s rural population. One of the major constraints of groundnut production is aflatoxin accumulation and insect infestation during storage. In our studies conducted at ICRISAT, the Purdue Improved Crop Storage (PICS) hermetic storage technology proved effective against insect infestation and aflatoxin accumulation during storage. To facilitate visual learning of the use of hermetic storage, a five minute GreenPHABLETTM video (GPV) in the local language was developed at ICRISAT. A 3-month long experiment was conducted in collaboration with an NGO Samatha of Penugonda in Anantapur district of Andhra Pradesh, India to assess the dissemination potential of GPV. A survey conducted among 30 farmers who received the video, revealed that about 80% of farmers received the video from a fellow farmer and only 20 per cent farmers received from the extension agents. Majority of the farmers received the video on their mobile phones through "Share It" (73.3%) and 13.3 per cent received via "Bluetooth", further 10 per cent reported through "WhatsApp" and while only 3.3% received it through the computer by USB Copy. After three months, 300 farmers from40 villages received the GPV, while our 30 respondents shared the GPV with 150 farmers and screened the GPV to 200 farmers. The experiment showsthat GPV can be an effective tool for spreading information about the groundnut hermetic storage technology and other agricultural innovations.